2011
DOI: 10.1186/1741-7015-9-71
|View full text |Cite
|
Sign up to set email alerts
|

FTO gene polymorphisms and obesity risk: a meta-analysis

Abstract: BackgroundThe pathogenesis of obesity is reportedly related to variations in the fat mass and an obesity-associated gene (FTO); however, as the number of reports increases, particularly with respect to varying ethnicities, there is a need to determine more precisely the effect sizes in each ethnic group. In addition, some reports have claimed ethnic-specific associations with alternative SNPs, and to that end there has been a degree of confusion.MethodsWe searched PubMed, MEDLINE, Web of Science, EMBASE, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
149
2
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 71 publications
(110 reference statements)
15
149
2
12
Order By: Relevance
“…In the large meta-analysis of GWAS, thus far performed with 123,865 individuals of European ancestry, the FTO locus was confirmed as one of the 32 variants associated with BMI with p-values \5 9 10 -8 (Speliotes et al 2010;Speakman et al 2011). A significant association between rs9939609 SNP of FTO gene and obesity, with an overall odds ratio (OR) for obesity of 1.31 under per-allele comparison, was reported in another meta-analysis including 111,571 subjects (Peng et al 2011).…”
Section: Introductionmentioning
confidence: 77%
“…In the large meta-analysis of GWAS, thus far performed with 123,865 individuals of European ancestry, the FTO locus was confirmed as one of the 32 variants associated with BMI with p-values \5 9 10 -8 (Speliotes et al 2010;Speakman et al 2011). A significant association between rs9939609 SNP of FTO gene and obesity, with an overall odds ratio (OR) for obesity of 1.31 under per-allele comparison, was reported in another meta-analysis including 111,571 subjects (Peng et al 2011).…”
Section: Introductionmentioning
confidence: 77%
“…Among those of European ancestry, all identified FTO SNPs significantly associated with obesity (located within the first intron) are part of a highly correlated linkage disequilibrium block. [4][5][6][7].…”
mentioning
confidence: 99%
“…Vimaleswaran et al showed a reduced, but still significant, effect of the rs1121980 polymorphism on both BMI and waist circumference in physically active individuals compared to an inactive group (20,374 European adults) [70]. Similarly, Andearsen et al [11] found an interaction between the FTO rs9939609 genotype and self-reported physical activity on BMI levels in the Inter99 study sample.…”
Section: Fto and Physical Activity (Pa)mentioning
confidence: 97%
“…The effect of the variant of FTO on adiposity varies among different populations [20]. In an Asian population, initial studies did not confirm the role of FTO.…”
Section: Fto and Obesity In Different Ethnic Groupsmentioning
confidence: 99%
See 1 more Smart Citation